Deposisi Lapisan Fe-Si-Al-Mg pada Baja Karbon dengan Teknik Pemaduan Mekanik [Deposition of Fe-Si-Al-Mg Coatings Using Mechanical Alloying Technique] - Lusita; Fahdiran, Riser; Sudiro, Toto; Hermanto, Bambang (Jurnal Metalurgi, 2019)
Fe-Si-Al-Mg coatings by weight variation of ferrosilicon, Mg, and Al as 50(Fe-Si)-37.5Al-12.5Mg, 50(Fe-Si)-25Al-25Mg, and 50(Fe-Si)-12.5Al-37.5Mg have been prepared on low carbon steel substrate using the mechanical alloying technique. The coatings were studied using XRD (x-ray diffractometer) to comprehend the phase formed on the substrate and OM (optical microscopy) to measure the coating thickness. Based on XRD and OM characterization, Fe-Si-Al-Mg coatings were successfully deposited on the low carbon steel substrate. Fe-Si-Al-Mg layers are composed by intermetallic phases of FeSi2, Mg2Si, and Al0.7Fe3Si0.47. Each composition shows different coating thickness that tends to decreases with the increase of magnesium concentration and the reduction of aluminum concentration.